МАРКЕТИНГТІК ТЕХНОЛОГИЯЛАР КƏСІПОРЫННЫҢ МАҢЫЗДЫ ҚҰРАЛЫ РЕТІНДЕ (Journal of Economic Research & Business Administration, 2015)
This article discusses the marketing techniques as important tools in their enterprise and analyzing these problems in use.